Bioencapsulated MXene Flakes for Enhanced Stability and Composite Precursors. (9th September 2020) - Krecker, Michelle C.; Bukharina, Daria; Hatter, Christine B.; Gogotsi, Yury; Tsukruk, Vladimir V.
Abstract: Here it is shown that Ti3 C2 T x MXene flakes can be co‐assembled with recombinant silk fibroin in aqueous suspensions with silk fibroin nanolayers uniformly covering individual flakes. These bioencapsulated flakes evolve with time due to the gradual growth of silk bundles having β‐sheet secondary organization with unique nanofibrillar morphologies extending across flake edges and forming long fringes around individual MXene flakes. This spontaneous reorganization of recombinant silk suggests surface template‐initiated formation of intramolecular hydrogen bonding of silk backbones assisted by intermolecular electrostatic and hydrogen bonding with the MXene flake. The formation of dense and hydrophobic β‐sheets results in development of a protective shell that hinders the surface oxidation of Ti3 C2 T x in colloidal solution in water and significantly extends the storage life of the individual MXene flakes. Moreover, assembly into organized laminated composites with individual bioencapsulated flakes tightly interconnected via biopolymer bundles and hairs produces robust freestanding electrically conductive membranes with enhanced transport properties. Abstract : Bioencapsulated MXene flakes are made via mixing Ti3 C2 T x MXene and recombinant Bombyx mori worm cocoon silk in an aqueous suspension at ambient conditions. These silk fibroin‐modified MXene bio‐hybrid materials evolve over time due to the gradual change of silk from an amorphous morphology into nanofibrils and assemble into robust, electrically conductive, free‐standing, organized laminated composites and separation membranes under vacuum‐assisted filtration.